The phenotypic presentation of adult individuals with SLC6A1-related neurodevelopmental disorders - Johannesen, Katrine M.; Nielsen, Jimmi; Sabers, Anne; Isidor, Bertrand; Kattentidt-Mouravieva, Anja A.; Zieglgänsberger, Dominik; Heidlebaugh, Alexis R.; Oetjens, Kathryn F.; Vidal, Anna Abuli; Christensen, Jakob; Tiller, Jacob; Freed, Amber N.; et al. (Frontiers in Neuroscience, 2023)
Introduction SLC6A1 is one of the most common monogenic causes of epilepsy and is a well-established cause of neurodevelopmental disorders. SLC6A1-neurodevelopmental disorders have a consistent phenotype of mild to severe intellectual disability (ID), epilepsy, language delay and behavioral disorders. This phenotypic description is mainly based on knowledge from the pediatric population. Method Here, we sought to describe patients with SLC6A1 variants and age above 18 years through the ascertainment of published and unpublished patients. Unpublished patients were ascertained through international collaborations, while previously published patients were collected through a literature search. Results A total of 15 adult patients with SLC6A1 variants were included. 9/13 patients had moderate to severe ID (data not available in two). Epilepsy was prevalent (11/15) with seizure types such as absence, myoclonic, atonic, and tonic–clonic seizures. Epilepsy was refractory in 7/11, while four patients were seizure free with lamotrigine, valproate, or lamotrigine in combination with valproate. Language development was severely impaired in five patients. Behavioral disorders were reported in and mainly consisted of autism spectrum disorders and aggressive behavior. Schizophrenia was not reported in any of the patients. Discussion The phenotype displayed in the adult patients presented here resembled that of the pediatric cohort with ID, epilepsy, and behavioral disturbances, indicating that the phenotype of SLC6A1-NDD is consistent over time. Seizures were refractory in >60% of the patients with epilepsy, indicating the lack of targeted treatment in SLC6A1-NDDs. With increased focus on repurposing drugs and on the development of new treatments, hope is that the outlook reflected here will change over time. ID appeared to be more severe in the adult patients, albeit this might reflect a recruitment bias, where only patients seen in specialized centers were included or it might be a feature of the natural history of SLC6A1-NDDs. This issue warrants to be explored in further studies in larger cohorts.